DATA BASE DEVELOPMENT AND EVALUATION OF EARTHQUAKE DAMAGE REPORTS UNDER THE SEISIMPACT-THES SYSTEM - Savvaidis, P.; Doukas, I.; Hatzigogos, Th.; Tziavos, I. N.; Kiratzi, A.; Roumelioti, Z.; Savvaidis, A.; Theodulidis, N.; Drakatos, G.; Koutoupes, S.; Karantonis, G.; Sotiriadis, A. (Bulletin of the Geological Society of Greece, 2004)
One of the scopes of the SEISIMPACT-THES project is to organize into digital form and evaluate the records of reported damage, related to the occurrence of the 1978 Thessaloniki earthquake (Mw=6.5). For the exploitation of these data, an advanced Information System is under development that will include: • A properly designed database • A Geographic Information System containing all the necessary data (after digitization and corrections) enriched with more recent data, as well as topographic, geological and geophysical data of the region (metropolitan area of Thessaloniki) • A model system of accessing the above via the web and mobile devices The basic data for the implementation of the project are derived from the archives of the Agency for the Relief of Seismic Catastrophes in Northern Greece (YASBE). The data are included in the forms of inspection of buildings carried out in Thessaloniki shortly afterwards the 1978 earthquake. It is estimated that there are roughly 63,000 building inspection forms in the region of Thessaloniki. The exploitation of this rich database with the description on the damage that the buildings suffered will result in a complete electronic database properly standardized so that it can be linked to the geographic data of a Geographic Information System. The database structure will allow multiple queries and processes to study in depth the behavior of buildings in Thessaloniki, and its correlation with other geological, geophysical, geotechnical factors